Transcendental Communication in Suluk Worship and Its Implementation to The Social Life of Worshippers in Dayah Darul Ulum Abu Lueng Ie Aceh Besar - Teuku Faisal; Syukur Kholil; Syawaluddin Nasution (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study examines the implementation of transcendental communication in the Suluk congregation at Dayah Darul Ulum Abu Lueng Ie, Aceh Besar. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, with the main subjects being the leaders and teachers of the dayah who guide the congregation in the Suluk process. Analysis was conducted to understand the spiritual experience of the congregation and its impact on their social lives. The results of the study indicate that transcendental communication in Suluk includes stages such as taharah (physical and spiritual cleansing) and tausiyah (spiritual guidance). Personal guidance from a cleric or mursyid plays an important role in helping the congregation reach a higher spiritual level. This process is carried out through the practice of dhikr and tafakur, which strengthens the vertical relationship with God and forms a positive social attitude. The impact of transcendental communication is not only limited to increasing individual spirituality, but is also seen in strengthening character, social responsibility, social awareness, and the active involvement of the congregation in social and charitable activities. Solidarity within the community also increases as a result of this process. However, several challenges are still encountered, such as limited spiritual understanding of the congregation, lack of continuity of practice, limited involvement of the mursyid, and negative influence of the media. Therefore, a more in-depth educational approach, structured guidance, and wise media management are needed to optimise the impact of transcendental communication in the social life of the congregation.